2018
DOI: 10.1063/1.5027080
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface hydroxyl groups on heat capacity of mesoporous silica

Abstract: This paper quantifies the effect of surface hydroxyl groups on the effective specific and volumetric heat capacities of mesoporous silica. To achieve a wide range of structural diversity, mesoporous silica samples were synthesized by various methods, including (i) polymer-templated nanoparticlebased powders, (ii) polymer-templated sol-gel powders, and (iii) ambigel silica samples dried by solvent exchange at room temperature. Their effective specific heat capacity, specific surface area, and porosity were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Indeed, in this case, the band gap values were determined from the extrapolation of the slopes of the modified K-M functions versus energy to zero absorption (indirect allowed transition method, n = 2). However, the authors found that the TiO2/SBA-15 catalyst revealed an increase in the Eg (3.30 eV), which was ascribed to the smaller size of TiO2 particles in the prepared catalyst supported on SBA-15 [36,37]. In particular, in this study the variation of band gap (ΔEg) had not the same extent depending on the different titania precursors, but the following trend was observed: P25 > Kronos VLP > Mirkat 211.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in this case, the band gap values were determined from the extrapolation of the slopes of the modified K-M functions versus energy to zero absorption (indirect allowed transition method, n = 2). However, the authors found that the TiO2/SBA-15 catalyst revealed an increase in the Eg (3.30 eV), which was ascribed to the smaller size of TiO2 particles in the prepared catalyst supported on SBA-15 [36,37]. In particular, in this study the variation of band gap (ΔEg) had not the same extent depending on the different titania precursors, but the following trend was observed: P25 > Kronos VLP > Mirkat 211.…”
Section: Discussionmentioning
confidence: 99%
“…The SS solution can be expressed as mSiO 2 •nH 2 O, and possesses a large amount of water and hydroxyl group. 31 The hydroxyl groups can bind to the alumina due to its hydrophilic behavior. 32 TO can be expressed as CH 3 CH 2 OSi(OCH 2 CH 3 ) 3 , and possesses a large amount of -OCH 2 CH 3 moieties.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…We note again that thermodynamic quantities such as heat capacity do not apply on the ultrafast timescale, but considering an effective heat capacity provides a reasonable explanation for our observations. Nanoscale silica materials have specific heat capacities below 1 J/g K, 40 whereas solvents typically have higher heat capacities. In these specific nanomaterials, the estimated specific heat capacity for silica in the coated silica samples ranges from 0.73 to 0.84 J/g K, 40 depending on porosity, and the heat capacity of the ligandcoated substrates can range between 1.6 J/mL K and 4.18 J/g K (Tables 1 & S2).…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
“…Nanoscale silica materials have specific heat capacities below 1 J/g K, 40 whereas solvents typically have higher heat capacities. In these specific nanomaterials, the estimated specific heat capacity for silica in the coated silica samples ranges from 0.73 to 0.84 J/g K, 40 depending on porosity, and the heat capacity of the ligandcoated substrates can range between 1.6 J/mL K and 4.18 J/g K (Tables 1 & S2). 34 Additional information about the heat capacity estimates for these samples can be found in the Supporting Information.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
See 1 more Smart Citation